Cumulative Effects of Several Nonenzymatic Mechanisms on the Resistance of Pseudomonas aeruginosa to Aminoglycosides - El'Garch, Farid (American Society for Microbiology, 2007)
Screening of a Tn5-Hg insertional library (12,000 clones) constructed in wild-type Pseudomonas aeruginosa strain PAO1 identified four genes (namely, galU, nuoG, mexZ, and rplY) whose disruption individually led to increased resistance to aminoglycosides (means of twofold). Inactivation of these genes was associated with (i) impaired outer membrane uptake, (ii) reduced active transport, (iii) increased MexXY-OprM-mediated active efflux, and (iv) alteration of target of aminoglycosides, respectively. In addition, suppression of the gene rplY, which codes for ribosomal protein L25, was found to result in both moderate upregulation of the efflux system MexXY-OprM and hypersusceptibility to β-lactam antibiotics. Construction of double, triple, and quadruple mutants demonstrated cumulative effects of the different mechanisms on aminoglycoside resistance, with MICs increasing from 16- to 64-fold in the quadruple mutant compared to the wild-type strain PAO1. Altogether, these results illustrate how P. aeruginosa may gradually develop high resistance to these antibiotics via intrinsic (i.e., nonenzymatic) mechanisms, as in cystic fibrosis patients.